2011
DOI: 10.1088/0957-4484/22/12/125705
|View full text |Cite
|
Sign up to set email alerts
|

Light absorption mechanism in single c-Si (core)/a-Si (shell) coaxial nanowires

Abstract: We have carried out detailed investigations on the light absorption mechanism in single crystalline silicon (c-Si) (core)/amorphous Si (a-Si) (shell) coaxial nanowires (NWs). Based on the Lorenz-Mie light scattering theory, we have found that the light absorption in the coaxial NWs relies on the leaky mode resonances and that the light absorption can be optimized towards photovoltaic applications when the a-Si shell thickness is about twice the c-Si core radius. The photocurrent has been found to be enhanced u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…Despite the antennaeffect-mediated strong absorption at short wavelengths, the overall performance of SNSCs is still far from expectation due to the narrow resonant bands and the relatively low absorption at long wavelengths. To improve the lightharvesting performance, properly engineering the structure parameters and cross-sectional morphology of the nanowires has been widely discussed in recent literatures [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It was shown that the light absorption in nanowire devices could be effectively engineered through control over the size, geometry and orientation of the nanostructure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the antennaeffect-mediated strong absorption at short wavelengths, the overall performance of SNSCs is still far from expectation due to the narrow resonant bands and the relatively low absorption at long wavelengths. To improve the lightharvesting performance, properly engineering the structure parameters and cross-sectional morphology of the nanowires has been widely discussed in recent literatures [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It was shown that the light absorption in nanowire devices could be effectively engineered through control over the size, geometry and orientation of the nanostructure [8].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14]17,[20][21][22][23][24][25][26][27] For example, absorption or scattering cross sections have been estimated qualitatively, 17,[20][21][22][23] while in other works wavelength-dependent photocurrent measurements performed on single NW PV devices were used to assign quantitatively the resonances of NW optical cavities. [13][14][15] Concurrent with experiments, numerical and analytical calculations of the resonant modes and key optical figures of merit (e.g.…”
mentioning
confidence: 99%
“…absorption efficiency and scattering cross section) for NW optical cavities have been reported. 13,14,20,21,[24][25][26][27] However, systematic studies of design rules for enhancing and tuning light absorption at broad-range wavelengths in NWs and their assembled structures have not been reported. In this study, we address these issues in Si NWs with modulated material compositions and cross-sectional geometries using numerical simulations, and moreover, elucidate the optical properties of single-and multi-layer arrays assembled the NW building blocks.…”
mentioning
confidence: 99%
“…The periodic boundary condition is used in z direction to treat the NWs as infinitely long, which has been well applied to describing the light scattering and absorption of various single NWs. 7,10 The light source is a broadband (300-1200 nm) plane wave perpendicular to NWs axis (along in y-axis), covering the major solar spectrum AM1.5. The mesh grid is set to 3 nm over the entire simulation volume, with a refinement of 2 nm over the volume occupied by the absorbing material.…”
Section: Modeling Detailsmentioning
confidence: 99%